Latihan dan perkhidmatan perguruan Sekolah Inggeris dan Sekolah Vernakular di Negeri-Negeri Melayu Bersekutu, 1896-1941 / Siti Aisyah Abdullah - Siti Aisyah , Abdullah (2018)
The study aims to examine the training and services of English schools and Malay vernacular schools in the Federated Malay States (FMS) from 1896 to 1941 by assessing the extent to which there was a difference in the British government policy on the development of entry schemes, teacher training schemes, salary scheme and retirement schemes in English school and Malay vernacular school in the Federated Malay States (FMS) from 1896 to 1941. Evaluations are made based on the role of senior British officials, the Malay King and education officials in establishing this disparity gap through three stages: the initial stage (1896-1905), the second stage (1906-1917) and the third stage (1918-1941).In the first stage, senior British officials created a significant discrepancy between the English schools and the Malay vernacular schools to strengthen their political and economic position. European headmasters received better salary and retirement scheme as they contributed significantly in improving education at first-class English schools. Although the British government provided quality training for teachers at English school, they were unable to enjoy a satisfactory salary and retirement scheme due to their poor performance. Contradictorily, the British government deliberately provided teacher training of low quality for Malay vernacular schools and encouraged Malay children to continue living in rural areas. This step was aimed at producing better generation of farmers, fishermen, carpenters and craftsmen. In the second phase, this gap began to diminish with the establishment of the Federal Council in 1909 following the appointment of Sir Arthur Henderson Young as the High Commissioner. The Federal Council provided a platform for the Malay Rulers and some unofficial European members to raise the weaknesses inherent in the Malay vernacular education system. This development not only provided the appointment of R.O. Winstedt as the Assistant Director of Education,who expedited the progress of the Malay vernacular education system, but also led to higher academic qualifications among trainee teachers at the Malay Teaching College. The third level was a turning point in the history of the development of education system, training and teaching services in the FMS when European teachers with relevant expertise were recruited to develop teaching training at English schools and Malay vernacular schools. At this stage, the involvement of the Malay King, nobility and education officials in Malay vernacular education had resulted vi in Malay vernacular school teachers enjoying better entry schemes, teacher training schemes, salary schemes and retirement schemes as compared to the first and second stage.